Training Basic Visual Attention Leads to Changes in Responsiveness to Social‐Communicative Cues in 9‐Month‐Olds. Issue 3 (24th April 2017) - Forssman, Linda; Wass, Sam V.
Abstract : This study investigated transfer effects of gaze‐interactive attention training to more complex social and cognitive skills in infancy. Seventy 9‐month‐olds were assigned to a training group ( n = 35) or an active control group ( n = 35). Before, after, and at 6‐week follow‐up both groups completed an assessment battery assessing transfer to nontrained aspects of attention control, including table top tasks assessing social attention in seminaturalistic contexts. Transfer effects were found on nontrained screen‐based tasks but importantly also on a structured observation task assessing the infants' likelihood to respond to an adult's social‐communication cues. The results causally link basic attention skills and more complex social‐communicative skills and provide a principle for studying causal mechanisms of early development.